Genomic diversity of toxigenic Vibrio cholerae O1 biovar El Tor strains isolated during three waves of the 7th cholera pandemic - Nina I. Smirnova; D. A. Rybal’chenko; Yu. V. Lozovsky; Ya. M. Krasnov; E. Yu. Shchelkanova; A. V. Fedorov; V. V. Kutyrev (Инфекция и иммунитет)
Introduction. High genome variability of the 7th cholera pandemic agent, V. cholerae El Tor, led to emergence of genovariants with distinct set of altered genes. The aim of the work was to analyze the dynamics of changes in pathogenicity, epidemicity as well as drug resistance and phylogeny in toxigenic strains of V. cholerae El Tor isolated in Russia and endemic regions during three waves of ongoing pandemic. Materials and methods. We used whole-genome nucleotide sequences of 155 strains, obtained by us (42) and taken from the NCBI Genbank (113). DNA sequencing was performed on Ion PGM platform. Phylogenetic relations were determined based on the Bayesian analysis of core SNPs obtained using Snippy 4.6 software package. Antibiotic resistance was assessed applying disk diffusion test. Results. SNP data revealed that the studied strains (1970–2023) might be divided into three clusters. A clear correlation between each-cluster strain genotype and relevant isolation timing was observed. Separation of genetically altered cluster II and III strains isolated during the 2nd and 3rd waves of the pandemic from typical cluster I strains is associated with acquisition of new DNA regions and mutations in pathogenicity and drug resistance genes. Due to different combination of mutations, cluster III strains are genetically heterogeneous. Genome comparison showed that this diversity increased dramatically during the 3rd wave, which led to emergence of new genovariants with higher pathogenic and epidemic potential. It is demonstrated that antibiotic resistance in strains both from endemic regions and Russia over the past 30 years (1993–2023) has undergone significant changes. Thereat, the changing drug resistance clearly correlated with the occurrence of mutations in various pathogenicity genes. Conclusion. It is shown that over the past two decades the agent genome underwent a rather rapid change resulting in emergence of various genovariants. A change in the pathogen variants in Russia has been established. Strains combining genetic markers of hyper-virulence and multiple drug resistance are of particular concern. Genome variability of the strains identified in points at a need for constant genomic surveillance to obtain data on altering epidemically important properties for timely generation of new diagnostic and preventive means.